Using Least Square for Develop a New Formation Resistivity Factor Correlation and Relationship between the Salinity and the Corrosion - Mazeb, Neima; AlFadil, Nassr (Libyan Journal for Engineering Research, 2017)
Formation resistivity factor (Fr),introduced by Archie , is an important parameter for electric log interpretation .It is defined as the resistivity of rock fully saturated with brine (Ro) divided by the resistivity of brine (Rw). This factor is function of porosity, resistivity, tortuosity and cementation factor, which are consequently affected also by particle size and degree of compaction .Formation resistivity factor is usually determined experimentally or by using empirical approach. During the present paper, we try to develop a new formation resistivity factor (Fr) correlation based on statistical methods, Least square, by taking into account different parameter such as brine salinity, particle size and degree of compaction. In addition, this study aims to determine the relationship between salinity and corrosion.